APPLYING RANGE OF MOTION TO OVERCOME PHYSICAL MOBILITY DISORDERS IN ISCHEMIC STROKE PATIENTS: A CASE STUDY - Nur Fadlilah; Yurike Septianingrum; Lono Wijayanti; Umdatus Soleha (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2026)
Background: Stroke is a neurological condition caused by arterial occlusion or hypoperfusion that leads to impaired neurological function and disability. Impaired physical mobility is a common consequence requiring targeted nursing interventions. Objectives: This case study aims to describe a comprehensive nursing care process for a stroke patient with impaired physical mobility through structured Range of Motion (ROM) therapy. Methods: A descriptive case study was conducted on one ischemic stroke patient. Data were obtained via interviews, physical assessment, observation, and documentation. ROM therapy was implemented following a detailed SOP, including passive and active-assistive movements, performed daily for 10–15 minutes. Results: Muscle strength improved from Grade 3 to Grade 4 in both left upper and lower extremities after three days of intervention. Conclusion: ROM therapy was effective in increasing muscle strength. Further research with longer durations and larger samples is recommended.